Development Of Scara Robotic Arm And Control System For Laboratory Automation - Koh, Johnny Siaw Paw (2002)
Recent developments in robotic system usage for material handlings, examine the various benefits of its applications in the chemical industry environment. In order to avoid the risk factor in chemical handling, various steps can be taken. One of the prominent methods is by substituting the human hands with the robotic arm in handling dangerous and erosive chemicals. It is with these reasons that this study was conducted with the primary objective to develop a system that would contribute towards encouraging a safety way of chemical testing and processing. This thesis provides an early analysis of robotic developments in the area The objective of this project is to develop a SCARA robotic arm and the intelligent control system. The design and development of this project involves three major sections. First section concerns about software programming, while the second section involves hardware construction and the final section deals with the graphic user interfacing (GUI). The hardware design can mainly be categorised into electrical design and mechanical design. Electrical design involves proper electrical wiring of input and output devices, power distributions, safety devices, interfacing devices and control components. The mechanical design is referred to the construction of the robot arm structures. These comprise mechanical drawings, mechanical simulations, mathematical calculations, as well as parts fabrication. On the other hand the design of software will consist of input and output assignments, program flow charts, robot-learning method and MINT programming. Design of GUI will involve Visual Basic (Professional Edition) programming. Basically, this project comprises several subsystems, namely: a sensor system, which is used to obtain data about the state of the mechanism and the environment, a controller and drivers, to guide the mechanism and the sensors in a desired manner, a planning and control system that decides on the actions and also consists of a power distributions system. The specified function of the robotic system is accomplished by intelligent interpretation of sensor information and mechanical actuations in term of plan, task and model.The entire robotic system was carefully and meticulously designed, constructed and tested. From the experimental results, it is proven that the proposed robotic system was successfully developed. This robotic arm can handle hazardous tasks in lab experiment specifically regarding chemical processing. Thus, reducing the risk on human.